Fourth-order cubic B-spline collocation method for hyperbolic telegraph equation - Singh, Suruchi; Singh, Swarn; Aggarwal, Anu (Mathematical sciences (Karaj, Iran), 2022)
In this article, a new method based on collocation of cubic B splines to find the numerical solution of one dimensional second-order hyperbolic partial differential equation subject to appropriate initial and boundary conditions has been proposed. The method is found to be high order accurate with compact support. Unconditional stability analysis of the proposed method has also been investigated. To justify the accuracy and efficacy of the proposed method, some numerical experiments are performed. The results obtained from the experiments are compared with the exact solution and the existing methods in literature.